Anti-aging PPO resin for copper-clad plate and preparation method of anti-aging PPO resin

By introducing amination lignin and ZnO/ZIF-8-NH2 composite additives into polysenol resin and using epoxidized polysenol as a crosslinking agent, the aging resistance of polysenol resin in copper clad plate applications is solved. The problem of insufficient results significantly improves the aging resistance and mechanical properties of the resin.

CN119264638AActive Publication Date: 2025-01-07JIANG SU YAO HONG ELECTRONICS CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411426223.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-07
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

The existing polystyrene alcohol resins have problems with insufficient aging resistance and mechanical properties in copper clad applications, especially due to the compatibility and mobility of additives and resins, which lead to limited aging resistance.

Method used

By introducing amination lignin and ZnO/ZIF-8-NH2 composite additives and using epoxidized polyphenylene ether as crosslinking agents, aging resistance and mechanical properties are enhanced.

Benefits of technology

It improves the aging resistance and mechanical properties of the resin, making it have higher bending strength and stability after curing, and is suitable for copper clad applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of anti-aging resin, and particularly discloses anti-aging PPO resin for a copper-clad plate and a preparation method of the anti-aging PPO resin. According to the method, lignin is aminated through a mixed solution of diethylenetriamine and 2, 2 '-bipyridine-6, 6'-diamine to prepare aminated lignin, and ZnO / ZIF-8-NH2 is prepared through a one-pot method. The molecular weight of polyphenyl ether is regulated and controlled by bisphenol A, and micromolecular polyphenyl ether is prepared. The preparation method comprises the following steps: reacting micromolecular polyphenyl ether with a dispersion liquid of ZnO / ZIF-8-NH2 and aminated lignin under a certain condition to obtain the composite additive. Uniformly mixing the polyphenyl ether, the composite additive and the epoxidized polyphenyl ether to obtain the anti-aging PPO resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-aging resins, in particular to an anti-aging PPO resin for copper clad laminates and a preparation method thereof. Background Art

[0002] Polyphenylene oxide resin (PPO resin) is a polymer material with excellent heat resistance, corrosion resistance and electrical insulation properties. It has a wide range of applications in the fields of electronics, electrical, aviation, etc. With the continuous advancement of science and technology, the performance requirements for polyphenylene oxide resins are getting higher and higher, especially in terms of aging resistance. In order to improve the aging resistance of polyphenylene oxide resins, researchers have conducted in-depth research by modifying the molecular structure of polyphenylene oxide resins, adding anti-aging agents, and adopting new polymerization methods. However, in the application process of copper clad laminates, its aging resistance still needs to be further improved. In the prior art, monomers with good aging resistance, such as styrene, dicyandiamide, etc., are usually introduced into polyphenylene oxide resins to improve the aging resistance of the resin. Some also improve the aging resistance of polyphenylene oxide resins by adding anti-aging agents or ultraviolet absorbers, but the additives of such substances have compatibility and migration problems with polyphenylene oxide resins, resulting in limited aging resistance and decreased mechanical properties.

[0003] In summary, it is of great significance to prepare an aging-resistant PPO resin for copper clad laminates and a preparation method thereof. Summary of the invention

[0004] The object of the present invention is to provide an aging-resistant PPO resin for copper-clad laminates and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] An aging-resistant PPO resin for copper-clad laminate and a preparation method thereof, comprising the following steps:

[0006] Step 1: Add lignin to a mixed solution of diethylenetriamine and 2,2'-bipyridine-6,6'-diamine, then add NaOH, heat to 80-100°C, stir evenly, drop formaldehyde, react for 3-5 hours, adjust the pH to 11-13, continue to react for 4-6 hours, wash with n-propanol several times and dry to obtain aminated lignin.

[0007] Step 2: (1) Mixing zinc acetate methanol solution and potassium hydroxide methanol solution, heating to 60-80° C. and stirring for 24-36 hours, centrifuging to remove the solvent at high speed, washing the precipitate with methanol and deionized water, and drying to obtain ZnO nanomaterials; (2) Dissolving zinc acetate in methanol to obtain solution A, dissolving 2-methylimidazole and 2-aminobenzimidazole in methanol to obtain solution B, ultrasonically dispersing ZnO nanomaterials in solution A, adding solution B under stirring at room temperature, stirring and mixing for 2-3 hours, centrifuging, washing the precipitate with methanol, and drying to obtain ZnO / ZIF-8-NH2.

[0008] Step 3: Add polyphenylene ether to toluene, then add bisphenol A, heat to 70-80°C and stir for 1-3 hours, add dibenzoyl peroxide, continue to react for 3-4 hours, filter the reaction system, wash with methanol, and obtain small molecule polyphenylene ether after drying.

[0009] Step 4: Add small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride to toluene, react at 70-80°C for 2-4 hours, remove excess epichlorohydrin by rotary evaporation, add toluene, add NaOH aqueous solution at 70-80°C, continue to react for 5-7 hours, cool to room temperature, filter, wash with methanol / water solution, and dry to obtain epoxidized polyphenylene ether.

[0010] Step 5: Add small molecule polyphenylene ether to chloroform and stir evenly; under nitrogen atmosphere, add triethylamine A, add a mixed solution of terephthaloyl chloride and chloroform dropwise at 0-5°C, and react for 1-3 hours; add triethylamine B, add a dispersion containing ZnO / ZIF-8-NH2 and aminated lignin, continue to react for 1-3 hours, extract with deionized water 3 times, filter the organic phase, and dry the precipitate to obtain a composite additive.

[0011] Step 6: Put polyphenylene ether, composite additives and epoxidized polyphenylene ether into a mixer and mix them evenly to obtain aging-resistant PPO resin.

[0012] Furthermore, the raw materials for aminated lignin in step 1 include the following components: by weight, 8 to 10 parts of lignin, 2 to 3 parts of diethylenetriamine, 0.2 to 0.3 parts of 2,2'-bipyridine-6,6'-diamine, 0.007 to 0.02 parts of NaOH, and 8 to 10 parts of formaldehyde.

[0013] Furthermore, in step 2, the concentration of the zinc acetate methanol solution is 1-2 mol / L, the concentration of the potassium hydroxide methanol solution is 3-6 mol / mL, and the volume ratio of the zinc acetate methanol solution to the potassium hydroxide methanol solution is 2:1; the concentration of solution A is 0.3-0.4 mol / mL, the volume ratio of solution A to solution B is 1:9, the concentration of 2-methylimidazole in solution B is 15-17 mol / mL, and the concentration of 2-aminobenzimidazole is 0.1-0.2 mol / mL.

[0014] Furthermore, in step three, the amount of bisphenol A added is 5-15% of the mass of the polyphenylene ether, and the amount of dibenzoyl peroxide added is 0.2-1% of the mass of the polyphenylene ether.

[0015] Furthermore, in step 4, the mass ratio of the small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride is 2:(0.5-2):0.02; the mass fraction of the NaOH solution is 20-40%, and the mass ratio of NaOH to the polyphenylene ether in the NaOH aqueous solution is 1:(4-6).

[0016] Furthermore, in step five, the mass ratio of terephthaloyl chloride to polyphenylene ether is 1:(5-7), and the mass ratio of triethylamine A to polyphenylene ether is 1:(6-8); the mass ratio of small molecule polyphenylene ether, ZnO / ZIF-8-NH2 and aminated lignin is 15:1:(1-3), and the amount of triethylamine B added is 1 / 5-3 / 5 of the mass of triethylamine A.

[0017] Furthermore, the polyphenylene ether described in step six is ​​60-70 parts, the composite additive is 25-30 parts, and the epoxidized polyphenylene ether is 1-2 parts.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The aging-resistant PPO resin in the present application is a composition comprising polyphenylene ether, composite additives and epoxidized polyphenylene ether.

[0020] (1) Aminated lignin and ZnO / ZIF-8-NH2 were introduced and grafted onto small molecule polyphenylene ether to form a composite additive, which was used to enhance the aging resistance of aging-resistant PPO resin and ensure its mechanical properties after curing.

[0021] Among them, the lignin molecule contains abundant functional groups, such as phenolic hydroxyl, carboxyl, methyl, etc., which makes the lignin have good aging resistance. At the same time, the functional groups can react with oxygen, water molecules, etc. to form stable chemical bonds; and the aromatic groups contained are not easy to react chemically, so that the lignin can still maintain relative stability under long-term exposure. However, due to the compatibility and dispersibility problems of lignin in PPO resin, it is necessary to further modify it; in the scheme, lignin is aminated to obtain aminated lignin, so that its surface contains amino groups, which are grafted on small molecular polyphenylene ether, thereby increasing the compatibility of lignin with PPO resin. In addition, the remaining amino groups on lignin can be cross-linked with the basic polyphenylene ether under the guidance of epoxidized PPO resin (cross-linking agent), increasing the reaction cross-linking. The final aging-resistant PPO resin has good mechanical properties and aging resistance after curing, so it can be better used in copper clad laminates.

[0022] Among them, ZnO / ZIF-8-NH2 is introduced, and amino groups are also used to graft with small molecular weight polyphenylene ether to increase compatibility. At the same time, compared with a single ZnO nanomaterial or ZIF-8-NH2 as an additive, there is a synergistic effect between the composite ZnO / ZIF-8-NH2 of the two, which can better improve the aging resistance. In addition, the composite of the two reduces the modification process and can be directly composited with small molecular weight polyphenylene ether.

[0023] (2) In order to further enhance the compatibility of the composite additive with the PPO resin and ensure its aging resistance and mechanical properties; the scheme further introduces a certain amount of epoxidized polyphenylene ether as a cross-linking agent to promote the grafting between the composite additive and the PPO resin, so that the final aging-resistant PPO resin has higher mechanical properties and aging resistance after curing. DETAILED DESCRIPTION

[0024] The following is a preferred implementation of the implementation case of the present invention. Obviously, the implementation case described is only a part of the implementation case of the present invention, not all of the implementation cases. For ordinary technicians in this technical field, all other implementation cases obtained by ordinary technicians in this field without creative work without departing from the principle of the implementation case of the present invention are within the scope of protection of the present invention.

[0025] It should be noted that, in the following embodiments, parts are parts by mass; the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: the CAS number of zinc acetate is 557-34-6, the CAS number of potassium hydroxide is 1310-58-3, the CAS number of 2-methylimidazole is 693-98-1, the CAS number of 2-aminobenzimidazole is 934-32-7, the CAS number of formic acid is 64-18-6, and the model of polyphenylene ether (PPO) is GFN1-111, CAS number of bisphenol A is 80-05-7, CAS number of dibenzoyl peroxide is 94-36-0, CAS number of epichlorohydrin is 106-89-8, CAS number of NaOH is 1310-73-2, CAS number of lignin is 8068-03-9, CAS number of 4-dimethylaminopyridine (DMAP) is 1122-58-3, formaldehyde is commercially available analytical grade, and CAS number of tetraethylammonium chloride is 56-34-8.

[0026] Implementation Case 1: Step 1: Add lignin (8 parts) to a mixed solution of diethylenetriamine (2 parts) and 2,2'-bipyridine-6,6'-diamine (0.2 parts), then add NaOH (0.007 parts), heat to 80°C, stir evenly, add formaldehyde (8 parts) dropwise and react for 3 hours to adjust the pH to 11, continue the reaction for 4 hours, wash with n-propanol and dry to obtain aminated lignin.

[0027] Step 2: (1) 1 mol / L zinc acetate methanol solution and 3 mol / mL potassium hydroxide methanol solution are mixed in a volume ratio of 2:1, heated and stirred at 60°C for 24 hours, centrifuged at high speed to remove the solvent, and the precipitate is washed with methanol and deionized water for 3 times respectively, and freeze-dried to obtain ZnO nanomaterials; (2) Zinc acetate is dissolved in methanol to obtain solution A (0.3 mol / mL). 2-Methylimidazole and 2-aminobenzimidazole are dissolved in methanol to obtain solution B (the concentration of 2-methylimidazole is 15 mol / mL and that of 2-aminobenzimidazole is 0.1 mol / mL), the volume ratio of solution A to solution B is 1:9, and ZnO nanomaterials are ultrasonically dispersed in solution A. Solution B is added under stirring at room temperature, stirred and mixed for 2 hours, centrifuged, and the precipitate is washed with methanol for 3 times. After drying, ZnO / ZIF-8-NH2 is obtained.

[0028] Step 3: first add polyphenylene ether PPO to toluene, then add bisphenol A, the amount of bisphenol A added is 5% of the polyphenylene ether, heat and stir at 70°C for 1 hour, add dibenzoyl peroxide, the amount of dibenzoyl peroxide added is 0.2% of the polyphenylene ether, continue to react for 3 hours, filter, wash with methanol 3 times, and obtain small molecule polyphenylene ether after drying.

[0029] Step 4: Add small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride to toluene, wherein the mass ratio of small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride is 2:0.5:0.02, react at 70°C for 2 hours, remove excess epichlorohydrin by rotary evaporation, add toluene, add 20wt% NaOH aqueous solution at 70°C, the mass ratio of NaOH to polyphenylene ether in the NaOH aqueous solution is 1:4, continue to react for 5 hours, cool to room temperature, filter, wash with methanol / water solution, and dry to obtain epoxidized polyphenylene ether.

[0030] Step 5: Add small molecule polyphenylene ether to chloroform, stir evenly, add triethylamine A under nitrogen atmosphere, the mass ratio of triethylamine A to polyphenylene ether is 1:5, add a mixed solution of terephthaloyl chloride and chloroform dropwise at 0-5°C, the mass ratio of terephthaloyl chloride to polyphenylene ether is 1:6, add triethylamine B after reacting for 1 hour, the amount of triethylamine B added is 1 / 5 of the mass of triethylamine A, add a dispersion containing ZnO / ZIF-8-NH2 and aminated lignin, wherein the mass ratio of small molecule polyphenylene ether, ZnO / ZIF-8-NH2 and aminated lignin is 15:1:1, continue the reaction for 1 hour, extract with deionized water 3 times, filter the organic phase and dry the precipitate to obtain a composite additive.

[0031] Step 6: Put 60 parts of polyphenylene ether, 25 parts of composite additives and 1 part of epoxidized polyphenylene ether into a mixer and mix them evenly to obtain an aging-resistant PPO resin.

[0032] Implementation Case 2: Step 1: Add lignin (9 parts) to a mixed solution of diethylenetriamine (2.5 parts) and 2,2'-bipyridine-6,6'-diamine (0.25 parts), then add NaOH (0.01 parts), heat to 90°C, stir evenly, add formaldehyde (9 parts) dropwise and react for 4 hours to adjust the pH to 12, continue the reaction for 5 hours, wash with n-propanol and dry to obtain aminated lignin.

[0033] Step 2: (1) 1.5 mol / L zinc acetate methanol solution and 4 mol / mL potassium hydroxide methanol solution are mixed in a volume ratio of 2:1, heated and stirred at 70°C for 30 hours, centrifuged at high speed to remove the solvent, and the precipitate is washed with methanol and deionized water for 3 times each, and freeze-dried to obtain ZnO nanomaterials; (2) Zinc acetate is dissolved in methanol to obtain solution A (0.35 mol / mL). 2-Methylimidazole and 2-aminobenzimidazole are dissolved in methanol to obtain solution B (the concentration of 2-methylimidazole is 16 mol / mL and that of 2-aminobenzimidazole is 0.15 mol / mL), the volume ratio of solution A to solution B is 1:9, and ZnO nanomaterials are ultrasonically dispersed in solution A. Solution B is added under stirring at room temperature, stirred and mixed for 2.5 hours, centrifuged, and the precipitate is washed with methanol for 3 times. After drying, ZnO / ZIF-8-NH2 is obtained.

[0034] Step 3: first add polyphenylene ether PPO to toluene, then add bisphenol A, the amount of bisphenol A added is 10% of the polyphenylene ether, heat and stir at 75°C for 2 hours, add dibenzoyl peroxide, the amount of dibenzoyl peroxide added is 0.3% of the polyphenylene ether, continue to react for 3.5 hours, filter, wash with methanol 3 times, and obtain small molecule polyphenylene ether after drying.

[0035] Step 4: Add small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride to toluene, wherein the mass ratio of small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride is 2:1:0.02, react at 70°C for 3 hours, remove excess epichlorohydrin by rotary evaporation, add toluene, add 30wt% NaOH aqueous solution at 70°C, the mass ratio of NaOH to polyphenylene ether in the NaOH aqueous solution is 1:5, continue to react for 6 hours, cool to room temperature, filter, wash with methanol / water solution, and dry to obtain epoxidized polyphenylene ether.

[0036] Step 5: Add small molecule polyphenylene ether to chloroform, stir evenly, add triethylamine A under nitrogen atmosphere, the mass ratio of triethylamine A to polyphenylene ether is 1:6, add a mixed solution of terephthaloyl chloride and chloroform dropwise at 0-5°C, the mass ratio of terephthaloyl chloride to polyphenylene ether is 1:7, add triethylamine B after reacting for 2 hours, the amount of triethylamine B added is 2 / 5 of the mass of triethylamine A, add a dispersion containing ZnO / ZIF-8-NH2 and aminated lignin, wherein the mass ratio of small molecule polyphenylene ether, ZnO / ZIF-8-NH2 and aminated lignin is 15:1:2, continue the reaction for 2 hours, extract with deionized water 3 times, filter the organic phase and dry the precipitate to obtain a composite additive.

[0037] Step 6: Put 65 parts of polyphenylene ether, 28 parts of composite additives, and 1.5 parts of epoxidized polyphenylene ether into a mixer and mix them evenly to obtain an aging-resistant PPO resin.

[0038] Implementation Case 3: Step 1: Add lignin (10 parts) to a mixed solution of diethylenetriamine (3 parts) and 2,2'-bipyridine-6,6'-diamine (0.3 parts), then add NaOH (0.02 parts), heat to 100°C, stir evenly, add formaldehyde (10 parts) dropwise and react for 5 hours to adjust the pH to 13, continue the reaction for 8 hours, wash with n-propanol and dry to obtain aminated lignin.

[0039] Step 2: (1) 2 mol / L zinc acetate methanol solution and 6 mol / mL potassium hydroxide methanol solution are mixed in a volume ratio of 2:1, heated and stirred at 80°C for 40 hours, centrifuged at high speed to remove the solvent, and the precipitate is washed with methanol and deionized water for 3 times respectively, and freeze-dried to obtain ZnO nanomaterials; (2) Zinc acetate is dissolved in methanol to obtain solution A (0.4 mol / mL). 2-Methylimidazole and 2-aminobenzimidazole are dissolved in methanol to obtain solution B (the concentration of 2-methylimidazole is 17 mol / mL and that of 2-aminobenzimidazole is 0.2 mol / mL), the volume ratio of solution A to solution B is 1:9, and ZnO nanomaterials are ultrasonically dispersed in solution A. Solution B is added under stirring at room temperature, stirred and mixed for 3 hours, centrifuged, and the precipitate is washed with methanol for 3 times. After drying, ZnO / ZIF-8-NH2 is obtained.

[0040] Step 3: first add polyphenylene ether PPO to toluene, then add bisphenol A, the amount of bisphenol A added is 15% of the polyphenylene ether, heat and stir at 80°C for 3 hours, add dibenzoyl peroxide, the amount of dibenzoyl peroxide added is 0.5% of the polyphenylene ether, continue to react for 4 hours, filter, wash with methanol 3 times, and obtain small molecule polyphenylene ether after drying.

[0041] Step 4: Add small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride to toluene, wherein the mass ratio of small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride is 2:1.7:0.02, react at 80°C for 4 hours, remove excess epichlorohydrin by rotary evaporation, add toluene, add 40wt% NaOH aqueous solution at 80°C, the mass ratio of NaOH to polyphenylene ether in the NaOH aqueous solution is 1:6, continue to react for 7 hours, cool to room temperature, filter, wash with methanol / water solution, and dry to obtain epoxidized polyphenylene ether.

[0042] Step 5: Add small molecule polyphenylene ether to chloroform, stir evenly, add triethylamine A under nitrogen atmosphere, the mass ratio of triethylamine A to polyphenylene ether is 1:8, add a mixed solution of terephthaloyl chloride and chloroform dropwise at 0-5°C, the mass ratio of terephthaloyl chloride to polyphenylene ether is 1:8, add triethylamine B after reacting for 3 hours, the amount of triethylamine B added is 3 / 5 of the mass of triethylamine A, add a dispersion containing ZnO / ZIF-8-NH2 and aminated lignin, wherein the mass ratio of small molecule polyphenylene ether, ZnO / ZIF-8-NH2 and aminated lignin is 15:1:3, continue the reaction for 3 hours, extract with deionized water 3 times, filter the organic phase and dry the precipitate to obtain a composite additive.

[0043] Step 6: Put 70 parts of polyphenylene ether, 30 parts of composite additives and 2-epoxidized polyphenylene ether into a mixer and mix them evenly to obtain an aging-resistant PPO resin.

[0044] Comparative Case 1: Step 1: Add lignin (9 parts) to a mixed solution of diethylenetriamine (2.5 parts) and 2,2'-bipyridine-6,6'-diamine (0.25 parts), then add NaOH (0.01 parts), heat to 90°C, stir evenly, add formaldehyde (9 parts) dropwise and react for 4 hours to adjust the pH to 12, continue the reaction for 5 hours, wash with n-propanol and dry to obtain aminated lignin.

[0045] Step 2: (1) 1.5 mol / L zinc acetate methanol solution and 4 mol / mL potassium hydroxide methanol solution are mixed in a volume ratio of 2:1, heated and stirred at 70°C for 30 hours, centrifuged at high speed to remove the solvent, and the precipitate is washed with methanol and deionized water for 3 times each, and freeze-dried to obtain ZnO nanomaterials; (2) Zinc acetate is dissolved in methanol to obtain solution A (0.35 mol / mL). 2-Methylimidazole and 2-aminobenzimidazole are dissolved in methanol to obtain solution B (the concentration of 2-methylimidazole is 16 mol / mL and that of 2-aminobenzimidazole is 0.15 mol / mL), the volume ratio of solution A to solution B is 1:9, and ZnO nanomaterials are ultrasonically dispersed in solution A. Solution B is added under stirring at room temperature, stirred and mixed for 2.5 hours, centrifuged, and the precipitate is washed with methanol for 3 times. After drying, ZnO / ZIF-8-NH2 is obtained.

[0046] Step 3: first add polyphenylene ether PPO to toluene, then add bisphenol A, the amount of bisphenol A added is 10% of the polyphenylene ether, heat and stir at 75°C for 2 hours, add dibenzoyl peroxide, the amount of dibenzoyl peroxide added is 0.3% of the polyphenylene ether, continue to react for 3.5 hours, filter, wash with methanol 3 times, and obtain small molecule polyphenylene ether after drying.

[0047] Step 4: Add small molecule polyphenylene ether to chloroform, stir evenly, add triethylamine A under nitrogen atmosphere, the mass ratio of triethylamine A to polyphenylene ether is 1:6, add a mixed solution of terephthaloyl chloride and chloroform at 0-5°C, the mass ratio of terephthaloyl chloride to polyphenylene ether is 1:7, add triethylamine B after reacting for 2 hours, the amount of triethylamine B added is 2 / 5 of the mass of triethylamine A, add a dispersion containing ZnO / ZIF-8-NH2 and aminated lignin, wherein the mass ratio of small molecule polyphenylene ether, ZnO / ZIF-8-NH2 and aminated lignin is 15:1:2, continue the reaction for 2 hours, extract with deionized water 3 times, filter the organic phase and dry the precipitate to obtain a composite additive.

[0048] Step 5: Put 65 parts of polyphenylene ether and 28 parts of composite additives into a mixer and mix them evenly to obtain aging-resistant PPO resin.

[0049] Comparative Example 1 is based on Implementation Example 2, without adding epoxidized polyphenylene ether.

[0050] Comparative Case 2: Step 1: Add lignin (9 parts) to a mixed solution of diethylenetriamine (2.5 parts) and 2,2'-bipyridine-6,6'-diamine (0.25 parts), then add NaOH (0.01 parts), heat to 90°C, stir evenly, add formaldehyde (9 parts) dropwise and react for 4 hours to adjust the pH to 12, continue the reaction for 5 hours, wash with n-propanol and dry to obtain aminated lignin.

[0051] Step 2: (1) 1.5 mol / L zinc acetate methanol solution and 4 mol / mL potassium hydroxide methanol solution were mixed in a volume ratio of 2:1, heated and stirred at 70°C for 30 hours, centrifuged at high speed to remove the solvent, and the precipitate was washed with methanol and deionized water for 3 times respectively, and freeze-dried to obtain ZnO nanomaterials; (2) Zinc acetate was dissolved in methanol to obtain solution A (0.35 mol / mL) and 2-methylimidazole was dissolved in methanol to obtain solution B (16 mol / mL). The volume ratio of solution A to solution B was 1:9. ZnO nanomaterials were ultrasonically dispersed in solution A, and solution B was added under stirring at room temperature. The mixture was stirred for 2.5 hours, centrifuged, and the precipitate was washed with methanol for 3 times. ZnO / ZIF-8 was obtained after drying.

[0052] Step 3: first add polyphenylene ether PPO to toluene, then add bisphenol A, the amount of bisphenol A added is 10% of the polyphenylene ether, heat and stir at 75°C for 2 hours, add dibenzoyl peroxide, the amount of dibenzoyl peroxide added is 0.3% of the polyphenylene ether, continue to react for 3.5 hours, filter, wash with methanol 3 times, and obtain small molecule polyphenylene ether after drying.

[0053] Step 4: Add small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride to toluene, wherein the mass ratio of small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride is 2:1:0.02, react at 70°C for 3 hours, remove excess epichlorohydrin by rotary evaporation, add toluene, add 30wt% NaOH aqueous solution at 70°C, the mass ratio of NaOH to polyphenylene ether in the NaOH aqueous solution is 1:5, continue to react for 6 hours, cool to room temperature, filter, wash with methanol / water solution, and dry to obtain epoxidized polyphenylene ether.

[0054] Step 5: Add the small molecule polyphenylene ether to chloroform, stir evenly, add triethylamine A under a nitrogen atmosphere, the mass ratio of triethylamine A to polyphenylene ether is 1:6, add a mixed solution of terephthaloyl chloride and chloroform dropwise at 0-5°C, the mass ratio of terephthaloyl chloride to polyphenylene ether is 1:7, add triethylamine B after reacting for 2 hours, the amount of triethylamine B added is 2 / 5 of the mass of triethylamine A, add a dispersion containing ZnO / ZIF-8 and aminated lignin, wherein the mass ratio of small molecule polyphenylene ether, ZnO / ZIF-8 and aminated lignin is 15:1:2, continue the reaction for 2 hours, extract with deionized water 3 times, filter the organic phase and dry the precipitate to obtain a composite additive.

[0055] Step 6: Put 65 parts of polyphenylene ether, 28 parts of composite additives, and 1.5 parts of epoxidized polyphenylene ether into a mixer and mix them evenly to obtain an aging-resistant PPO resin.

[0056] Comparative Case 2 is based on Implementation Case 2, except that ZnO / ZIF-8-NH2 is not added but ZnO / ZIF-8 is added instead.

[0057] Comparative Case 3: Step 1: Add lignin (9 parts) to a mixed solution of diethylenetriamine (2.5 parts) and 2,2'-bipyridine-6,6'-diamine (0.25 parts), then add NaOH (0.01 parts), heat to 90°C, stir evenly, add formaldehyde (9 parts) dropwise and react for 4 hours to adjust the pH to 12, continue the reaction for 5 hours, wash with n-propanol and dry to obtain aminated lignin.

[0058] Step 2: Zinc acetate is dissolved in methanol to obtain solution A (0.35 mol / mL). 2-Methylimidazole and 2-aminobenzimidazole are dissolved in methanol to obtain solution B (the concentration of 2-methylimidazole is 16 mol / mL, and that of 2-aminobenzimidazole is 0.15 mol / mL). The volume ratio of solution A to solution B is 1:9. Solution B is added to solution A under stirring at room temperature, and the mixture is stirred for 2.5 hours. The mixture is centrifuged, and the precipitate is washed three times with methanol. ZIF-8-NH2 is obtained after drying.

[0059] Step 3: first add polyphenylene ether PPO to toluene, then add bisphenol A, the amount of bisphenol A added is 10% of the polyphenylene ether, heat and stir at 75°C for 2 hours, add dibenzoyl peroxide, the amount of dibenzoyl peroxide added is 0.3% of the polyphenylene ether, continue to react for 3.5 hours, filter, wash with methanol 3 times, and obtain small molecule polyphenylene ether after drying.

[0060] Step 4: Add small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride to toluene, wherein the mass ratio of small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride is 2:1:0.02, react at 70°C for 3 hours, remove excess epichlorohydrin by rotary evaporation, add toluene, add 30wt% NaOH aqueous solution at 70°C, the mass ratio of NaOH to polyphenylene ether in the NaOH aqueous solution is 1:5, continue to react for 6 hours, cool to room temperature, filter, wash with methanol / water solution, and dry to obtain epoxidized polyphenylene ether.

[0061] Step 5: Add small molecule polyphenylene ether to chloroform, stir evenly, add triethylamine A under nitrogen atmosphere, the mass ratio of triethylamine A to polyphenylene ether is 1:6, add a mixed solution of terephthaloyl chloride and chloroform dropwise at 0-5°C, the mass ratio of terephthaloyl chloride to polyphenylene ether is 1:7, add triethylamine B after reacting for 2 hours, the amount of triethylamine B added is 2 / 5 of the mass of triethylamine A, add a dispersion containing ZIF-8-NH2 and aminated lignin, wherein the mass ratio of small molecule polyphenylene ether, ZIF-8-NH2 and aminated lignin is 15:1:2, continue the reaction for 2 hours, extract with deionized water 3 times, filter the organic phase and dry the precipitate to obtain a composite additive.

[0062] Step 6: Put 65 parts of polyphenylene ether, 28 parts of composite additives, and 1.5 parts of epoxidized polyphenylene ether into a mixer and mix them evenly to obtain an aging-resistant PPO resin.

[0063] Comparative Case 3 is based on Implementation Case 2, without adding ZnO nanomaterials.

[0064] Comparative Case 4: Step 1: (1) 1.5 mol / L zinc acetate methanol solution and 4 mol / mL potassium hydroxide methanol solution were mixed in a volume ratio of 2:1, heated and stirred at 70°C for 30 hours, centrifuged at high speed to remove the solvent, and the precipitate was washed with methanol and deionized water three times each, and freeze-dried to obtain ZnO nanomaterials; (2) Zinc acetate was dissolved in methanol to obtain solution A (0.35 mol / mL). 2-Methylimidazole and 2-aminobenzimidazole were dissolved in methanol to obtain solution B (the concentration of 2-methylimidazole was 16 mol / mL and that of 2-aminobenzimidazole was 0.15 mol / mL). The volume ratio of solution A to solution B was 1:9. ZnO nanomaterials were ultrasonically dispersed in solution A. Solution B was added under stirring at room temperature, stirred and mixed for 2.5 hours, centrifuged, and the precipitate was washed with methanol three times. ZnO / ZIF-8-NH2 was obtained after drying.

[0065] Step 2: first add polyphenylene ether PPO to toluene, then add bisphenol A, the amount of bisphenol A added is 10% of the polyphenylene ether, heat and stir at 75°C for 2 hours, add dibenzoyl peroxide, the amount of dibenzoyl peroxide added is 0.3% of the polyphenylene ether, continue to react for 3.5 hours, filter, wash with methanol 3 times, and obtain small molecule polyphenylene ether after drying.

[0066] Step 3: Add small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride to toluene, wherein the mass ratio of small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride is 2:1:0.02, react at 70°C for 3 hours, remove excess epichlorohydrin by rotary evaporation, add toluene, add 30wt% NaOH aqueous solution at 70°C, the mass ratio of NaOH to polyphenylene ether in the NaOH aqueous solution is 1:5, continue to react for 6 hours, cool to room temperature, filter, wash with methanol / water solution, and dry to obtain epoxidized polyphenylene ether.

[0067] Step 4: Add small molecule polyphenylene ether to chloroform, stir evenly, add triethylamine A under nitrogen atmosphere, the mass ratio of triethylamine A to polyphenylene ether is 1:6, add a mixed solution of terephthaloyl chloride and chloroform dropwise at 0-5°C, the mass ratio of terephthaloyl chloride to polyphenylene ether is 1:7, add triethylamine B after reacting for 2 hours, the amount of triethylamine B added is 2 / 5 of the mass of triethylamine A, add a dispersion containing ZnO / ZIF-8-NH2, wherein the mass ratio of small molecule polyphenylene ether to ZnO / ZIF-8-NH2 is 15:1, continue the reaction for 2 hours, extract with deionized water 3 times, filter the organic phase and dry the precipitate to obtain a composite additive.

[0068] Step 5: Put 65 parts of polyphenylene ether, 28 parts of composite additives, and 1.5 parts of epoxidized polyphenylene ether into a mixer and mix them evenly to obtain an aging-resistant PPO resin.

[0069] Comparative Example 4 is based on Implementation Example 2, without adding aminated lignin.

[0070] Test: Thermal aging test of implementation cases 1 to 3 and comparative cases 1 to 4: The obtained aging-resistant resin was extruded and granulated by a twin-screw extruder, which includes seven temperature zones, one of which is 215°C, the second is 225°C, the third is 230°C, the fourth is 240°C, the fifth is 250°C, the sixth is 250°C, and the seventh is 270°C. The screw speed is 500r / min. Then, it is placed in a flat vulcanizer for compression molding, and finally post-cured at 200°C for 3h, the pressure is 16Mpa, and the cured samples of implementation cases 1 to 3 and comparative cases 1 to 4 are placed in a vacuum drying oven for thermal aging, the thermal aging time is 200 hours, the vacuum drying oven temperature is 150°C, and the vacuum degree is -0.095MPa. The bending strength of the above implementation cases 1 to 3 and comparative cases 1 to 4 before and after thermal aging is tested in accordance with the national standard GB / T9341-2008.

[0071] Flexural strength before heat aging MPa Flexural strength after heat aging MPa Implementation Case 1 95.5 83.5 Implementation Case 2 98.7 87.9 Implementation Case 3 94.3 82.4 Comparative Case 1 93.2 79.2 Comparative Case 2 92.7 78.8 Comparative Case 3 91.3 72.1 Comparative Case 4 90.8 71.7

[0072] Comparative Case 1 is based on Implementation Case 2, without adding epoxidized polyphenylene ether. Not adding epoxidized polyphenylene ether leads to decreased compatibility between PPO resin and composite additives, thereby reducing the bending strength of the cured aging-resistant PPO resin before and after thermal aging. Comparative Case 2 is based on Implementation Case 2, without adding ZnO / ZIF-8-NH2 but adding ZnO / ZIF-8 instead. The dispersibility of ZnO / ZIF-8 without amino groups in the aging-resistant PPO resin decreases, resulting in decreased bending strength of the cured aging-resistant PPO resin before and after thermal aging. Comparative Case 3 is based on Implementation Case 2, without adding ZnO nanomaterials. After curing, the aging-resistant PPO resin without adding ZnO nanomaterials has a decreased degree of bending before and after thermal aging. Comparative Case 4 is based on Implementation Case 2, without adding aminated lignin. After curing, the aging-resistant PPO resin without adding aminated lignin has a decreased bending strength before and after thermal aging.

[0073] Finally, it should be noted that the above is only a preferred implementation case of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the implementation methods and features of the implementation methods of this application can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.

Claims

1. A method for preparing an aging-resistant PPO resin for copper-clad laminates, characterized in that: The following steps are involved: S1: adding lignin to a mixed solution of diethylenetriamine and 2,2'-bipyridine-6,6'-diamine, then adding NaOH, heating to 80-100°C, stirring evenly, adding formaldehyde dropwise, reacting for 3-5 hours, adjusting the pH to 11-13, continuing the reaction for 4-6 hours, washing, and drying to obtain aminated lignin; S2: (1) Mixing zinc acetate methanol solution and potassium hydroxide methanol solution, heating to 60-80°C and stirring for 24-36 hours, removing the solvent by high-speed centrifugation, washing, and drying to obtain ZnO nanomaterials; (2) Dissolving zinc acetate in methanol to obtain solution A, dissolving 2-methylimidazole and 2-aminobenzimidazole in methanol to obtain solution B, ultrasonically dispersing ZnO nanomaterials in solution A, adding solution B under stirring at room temperature, stirring and mixing for 2-3 hours, centrifuging, washing, and drying to obtain ZnO / ZIF-8-NH2; S3: adding polyphenylene ether to toluene, then adding bisphenol A, heating to 70-80°C and stirring for 1-3 hours, adding dibenzoyl peroxide, continuing the reaction for 3-4 hours, filtering the reaction system, washing, and drying to obtain small molecule polyphenylene ether; S4: adding small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride to toluene, reacting at 70-80° C. for 2-4 hours, removing excess epichlorohydrin by rotary evaporation, adding toluene, adding NaOH aqueous solution at 70-80° C., continuing the reaction for 5-7 hours, cooling to room temperature, filtering, washing and drying to obtain epoxidized polyphenylene ether; S5: Add small molecule polyphenylene ether to chloroform and stir evenly; under nitrogen atmosphere, add triethylamine A, add dropwise a mixed solution of terephthaloyl chloride and chloroform at 0-5°C, and react for 1-3 hours; add triethylamine B, add a dispersion containing ZnO / ZIF-8-NH2 and aminated lignin, continue to react for 1-3 hours, and post-treat to obtain a composite additive; S6: Evenly stir the polyphenylene ether, the composite additive and the epoxidized polyphenylene ether to obtain an aging-resistant PPO resin.

2. The method for preparing an aging-resistant PPO resin for copper-clad laminate according to claim 1, characterized in that: The raw materials of aminated lignin include the following components: by weight, 8-10 parts of lignin, 2-3 parts of diethylenetriamine, 0.2-0.3 parts of 2,2'-bipyridine-6,6'-diamine, 0.007-0.02 parts of NaOH, and 8-10 parts of formaldehyde.

3. The method for preparing an aging-resistant PPO resin for copper-clad laminate according to claim 1, characterized in that: In S2, the concentration of zinc acetate methanol solution is 1-2 mol / L, the concentration of potassium hydroxide methanol solution is 3-6 mol / mL, and the volume ratio of zinc acetate methanol solution to potassium hydroxide methanol solution is 2:1; the concentration of solution A is 0.3-0.4 mol / mL, the volume ratio of solution A to solution B is 1:9, the concentration of 2-methylimidazole in solution B is 15-17 mol / mL, and that of 2-aminobenzimidazole is 0.1-0.2 mol / mL.

4. The method for preparing an aging-resistant PPO resin for copper-clad laminate according to claim 1, characterized in that: In S3, the added amount of bisphenol A accounts for 5-15% of the mass of the polyphenylene ether, and the added amount of dibenzoyl peroxide accounts for 0.2-1% of the mass of the polyphenylene ether.

5. The method for preparing an aging-resistant PPO resin for copper-clad laminate according to claim 1, characterized in that: In S4, the mass ratio of small molecule polyphenylene ether, epichlorohydrin and tetraethylammonium chloride is 2:(0.5-2):0.02; the mass fraction of NaOH solution is 20-40%, and the mass ratio of NaOH to polyphenylene ether in the NaOH aqueous solution is 1:(4-6).

6. The method for preparing an aging-resistant PPO resin for copper-clad laminate according to claim 1, characterized in that: In S5, the mass ratio of terephthaloyl chloride to polyphenylene ether is 1:(5-7), and the mass ratio of triethylamine A to polyphenylene ether is 1:(6-8); the mass ratio of small molecule polyphenylene ether, ZnO / ZIF-8-NH2 and aminated lignin is 15:1:(1-3), and the amount of triethylamine B added is 1 / 5-3 / 5 of the mass of triethylamine A.

7. The method for preparing an aging-resistant PPO resin for copper-clad laminate according to claim 1, characterized in that: The raw materials of the aging-resistant PPO resin include the following components: by weight, 60-70 parts of polyphenylene ether, 25-30 parts of composite additives, and 1-2 parts of epoxidized polyphenylene ether.

8. The aging-resistant PPO resin prepared according to the method for preparing an aging-resistant PPO resin for copper-clad laminates according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Railway signal

    CA106898A

  • Routing of network traffic

    CA1310732C

  • Shoe tip

    CA64186A

  • Calf weaner

    CA94360A

  • Polyfunctional group polyphenylene ether resin and preparation method thereof

    CN104231259A